Structural Instability of a Biochemical Process - Grytsay, V.I. (Український фізичний журнал, 2010)
By the example of a mathematical model of a biochemical process, the structural instability of dynamical systems is studied by calculating the full spectrum of Lyapunov indices with the use of the generalized Benettin algorithm. For the reliability of the results obtained, the higher Lyapunov index determined with the orthogonalization of perturbation vectors by the Gram–Schmidt method is compared with that determined with the overdetermination of only the norm of a perturbation vector. Specific features of these methods and the comparison of their efficiencies for a multidimensional phase space are presented. A scenario of the formation of strange attractors at a change of the dissipation parameter is studied. The main regularities and the mechanism of formation of a deterministic chaos due to the appearance of a fold or a funnel, which leads to the uncertainty of the evolution of a biosystem, are determined. У роботi на прикладi математичної моделi бiохiмiчного процесу проведено дослiдження структурної нестiйкостi динамiчних систем за допомогою розрахунку повного спектра показникiв Ляпунова узагальненим алгоритмом Бенеттина. Для достовiрностi отриманих результатiв проведено порiвняння старших показникiв Ляпунова, знайдених з урахуванням ортогоналiзацiї векторiв збудження методом Грамa–Шмiдта, та при перевизначеннi лише норми вектора збудження. Наведено особливостi використання цих методiв та дано їх порiвняння за ефективнiстю для багатовимiрного фазового простору. Дослiджено сценарiй формування дивних атракторiв при змiнi параметра дисипацiї. Знайдено основнi закономiрностi виникнення детермiнованого хаосу в системах рiзної фiзичної природи.